2005
DOI: 10.1177/112067210501500615
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Triamcinolone Acetonide for Treatment of Central Retinal Vein Occlusion

Abstract: Intravitreal triamcinolone acetonide temporarily increases visual acuity in central retinal vein occlusion. It is accompanied by an increase in intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 45 publications
(80 reference statements)
0
43
0
2
Order By: Relevance
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] A disturbed balance of angiogenic and inflammatory cytokines has been reported to be associated with retinal vein occlusion, 20 and experimental investigations and clinical studies have suggested a temporary antioedematous and antiangiogenic effect of intravitreal triamcinolone in eyes with CRVO. 6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] A disturbed balance of angiogenic and inflammatory cytokines has been reported to be associated with retinal vein occlusion, 20 and experimental investigations and clinical studies have suggested a temporary antioedematous and antiangiogenic effect of intravitreal triamcinolone in eyes with CRVO. 6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] A disturbed balance of angiogenic and inflammatory cytokines has been reported to be associated with retinal vein occlusion, 20 and experimental investigations and clinical studies have suggested a temporary antioedematous and antiangiogenic effect of intravitreal triamcinolone in eyes with CRVO. 6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract. [21][22][23][24][25] In contrast, studies on intravitreal bevacizumab by Rosenfeld et al and other researchers showed an improvement in visual acuity, reduction in macular thickness, and only minor complications in patients with CRVOs, [26][27][28][29][30][31][32][33][34] so that intravitreal triamcinolone was rapidly exchanged by intravitreal bevacizumab for the treatment of CRVO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first reports on the use of IVTA for the treatment of CRVO by Greenberg et al [99] and Jonas et al [104], the number of reports on the use of IVTA as therapy of CRVO have increased exponentially [93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111]. In a prospective nonrandomized comparative study on 11 eyes with CRVO receiving an intravitreal injection of TA, compared with 6 eyes of a control group without intravitreal injection of TA, the gain in visual acuity was significantly (p = 0.003) higher in the study group [103].…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemamentioning
confidence: 99%
“…They have potent anti-inflammatory effects, can reduce vascular permeability, inhibit fibrin deposition and leukocyte movement, suppress homing and migration of inflammatory cells, stabilize endothelial cell tight junctions, and inhibit synthesis of VEGF, prostaglandins, and other cytokines [18]. Intravitreal injections of the lipophilic corticosteroid triamcinolone acetonide have been shown to produce benefits in eyes with RVO, but several adverse events have been noted (with elevated intraocular pressure [IOP] and cataract being the most common) [8,10,15,[21][22][23][24][25][26][27][28][29]. Other corticosteroids, however, have their own unique properties and may have different clinical profiles in intravitreal use [30].…”
Section: Introductionmentioning
confidence: 99%